Fatores associados à não adesão e à não aceitação da alimentação escolar por alunos de escolas públicas de tempo integral - Carvalho, Nágila Araújo de (2015)
The basic education has advanced towards full-time education, the student staying longer in school, increasing the number of meals served and the need to adapt the institutions to the new reality of school meals. The aim of the study was to identify adherence and acceptance to food and analyze the factors associated with non-adherence and non-acceptance of students from public schools full-time Goiânia. Cross-sectional study with students from six to 14 years in public school full-time. The consumption of meals on issues were investigated, served preparations, food distribution, food external to school and socioeconomic data, including nutritional assessment of students. Adherence to meals (snacks in the morning and afternoon and lunch) was defined as the effective consumption of four to five times / week and acceptance, this is the approval meals, by means of hedonic face five-point scale with cutoff 85.0%, being lower in mid-morning snack. Poisson regression performed to identify factors associated with non-adherence and non-acceptance of meals. Attended by 359 students, most were eutrophic, had six to 10 years old, belonging to the class C and mothers had nine years or more of study. Adherence was high for lunch and afternoon snack and low for a snack in the morning and for three meals together. The acceptance did not reach 85.0% in any of the meals. Factors associated with nonadherence were number of persons above four at home, consumer place the refectory, and the same uncomfortable and the negative evaluation of utensils. Factors associated with non-acceptance were age >10 years, female gender, the negative evaluation of utensils and inadequate food temperature. Most students adhered for lunch and afternoon snack, but not at the morning snack. Non-adherence and rejection were associated to demographic, social and related to food in schools. A monitoring of the program is essential if public resources invested appropriately, directed to public needs to which they relate. Acceptability tests are needed periodically including the assessment of adherence.